2010
DOI: 10.1089/cyber.2009.0094
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Young Adults' Use of Social Networking Sites

Abstract: Young people are increasingly using social networking sites (SNSs) like MySpace and Facebook to engage with others. The use of SNSs can have both positive and negative effects on the individual; however, few studies identify the types of people who frequent these Internet sites. This study sought to predict young adults' use of SNSs and addictive tendency toward the use of SNSs from their personality characteristics and levels of self-esteem. University students (N = 201), aged 17 to 24 years, reported their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
172
6
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(205 citation statements)
references
References 21 publications
13
172
6
14
Order By: Relevance
“…The habitual use of Facebook negatively affects behavioral relations [37]. Growing concerns have been raised about negative impact of SNSs such as legal and professional risks, extroversion and low conscientiousness, loneliness, personality traits and self-esteem issues [38,39]. Such information should alert policy-makers to advocate appropriate use of SNSs for education that can enrich learning climate without harming students’ behaviors and interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The habitual use of Facebook negatively affects behavioral relations [37]. Growing concerns have been raised about negative impact of SNSs such as legal and professional risks, extroversion and low conscientiousness, loneliness, personality traits and self-esteem issues [38,39]. Such information should alert policy-makers to advocate appropriate use of SNSs for education that can enrich learning climate without harming students’ behaviors and interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Given the association between Internet or SNS addiction and certain personality traits, it is possible that there will be an impact on patient care. 22,[27][28][29][30][31][32][33][34][35] Indeed, studies have shown that these same personality traits impact directly on work performance; 45,46 in health-related fields, this will have affect the quality of patient care. Therefore, it would be beneficial for future research to focus on the possibility of a direct link between these addictions and negative repercussions on patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive use of and addiction to Internet activities-including SNSs and online games-has been negatively associated with conscientiousness, honesty/humility and agreeableness and positively associated with neuroticism, narcissism and aggression. 22,[27][28][29][30][31][32][33][34][35] For medical students aiming to develop into caring health professionals, the implications of this addiction can have wide and detrimental consequences for society as a whole. It is important, therefore, to know the scale of the problem so that appropriate measures can be taken to combat it.…”
Section: -13mentioning
confidence: 99%
“…It is worth noting that numerous studies have reported that there is an association between low levels of conscientiousness and addiction (e.g., Buckner, Castille, Sheets, 2012;Kotov, Gamez, Schmidt, & Watson, 2010;Yang, Li, & Mingxin, 2006). In particular, Wilson, Fornasier, and White (2010) reported that individuals with low conscientiousness had higher levels of both SNS use and addictive tendencies. In addition, it has previously been reported that Facebook users are more likely than non-users to be low on conscientiousness (Ryan & Xenos, 2011).…”
Section: Future Research: Pathways To Problematic Facebook Usementioning
confidence: 99%